Progress towards Recognised Professional Status: The Australian Financial Planning Landscape in 2022 - Neilson, Ben (International Journal of Economics and Financial Issues, 2022)
Research seeks to measure the progress made towards achieving recognised professional status within the Australian financial planning sector. It identifies four key professional attributes derived from literature and applies these within a financial context using a tool designed to measure progress. Sample size consists of 1,093 useable responses recorded during a four-month period in 2022. Quantitative data collected using online survey and recorded using Likert mean scale with ANOVA analysis technique applied. Results aim to evidence progress and further advance financial theory by bridging a knowledge gap and evidencing the professional progress within the Australian financial planning sector.